The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/jsfa.3004
|View full text |Cite
|
Sign up to set email alerts
|

Role of rodents in transmission ofSalmonellaandCampylobacter

Abstract: Salmonella and Campylobacter are generally regarded as the most important food-borne pathogens in the world. Reduction or elimination of these pathogens in the first part of the food chain (on the farm) is important to prevent disease among consumers of animal products. In organic farming, elimination becomes more difficult, as food animals are allowed outdoors and have easy access to potential sources of hazardous pathogens. Whilst rodents are often associated by organic farmers with infrastructural damage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 54 publications
3
91
0
3
Order By: Relevance
“…Fecal prevalence of Salmonella in the current study also fell within previously reported ranges in wild rodents (33). In one study, none of the specimens from wild mice trapped in a major produce production region in California was positive for Salmonella (34).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Fecal prevalence of Salmonella in the current study also fell within previously reported ranges in wild rodents (33). In one study, none of the specimens from wild mice trapped in a major produce production region in California was positive for Salmonella (34).…”
Section: Discussionsupporting
confidence: 87%
“…With increasing trap success, there was a concurrent increase in the odds of shedding of Salmonella, suggesting that a possible density-dependent horizontal transmission mechanism occurs between rodents. This finding is supported by studies that have reported an increased risk of shedding with increased rodent density (33,42). High rates of rodent dispersal have also been associated with increased density (43), which may in turn facilitate emigration of infected rodents into new areas.…”
Section: Discussionsupporting
confidence: 57%
“…The control of Salmonella is difficult as Salmonella can remain in the environment. Rodents also play an important role in the persistence of salmonella in poultry farms [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Rodents also play an important role in the persistence of Salmonella in poultry farms (Meerburg and Kijlstra, 2007). All manure was scraped from floors and walls and all feeding and watering equipments were disinfected.…”
Section: Resultsmentioning
confidence: 99%